PERILAKU BERPACARAN REMAJA KOS-KOSAN DI KOTA RUTENG, KABUPATEN MANGGARAI, NTT - Ambros Leonangung Edu; Fransiska Jaiman Madu; Mariana Jediut; Petrus Redy Partus Jaya (Unika Santu Paulus Ruteng, 2020)
Research on the dating behavior of teens at boarding houses in Ruteng City consists of two parts - research on high school teenagers and college’s students teenagers. This report focuses on the results of research to students living at boarding houses. This study was designed to describe the dating behavior of teenage boarders in the Ruteng, Manggarai Regency. Sexual dating behavior that drives this research is about emerging forms of thinking about sexual drive for couples. Various forms, such as holding hands, hugging, kissing, touching sensitive body parts, and sexual intercourses. Based on this concept, dating behavior is grouped into 4 activities, dating, necking, petting, and intercourses. Getting data, the team used survey by quantitative approach. Data collection techniques consisted of questionnaires, interviews, and observations. Questions related to student dating behaviors. Questionnaire was supported by interview and observation. The total participants were 320 students who were dating in Ruteng. From the total and 95% confidence level, the team determined margin of error totally 5.3%. Data were analyzed by descriptive statistical techniques and non-parametric statistics. Descriptive statistics were used to describe the condition of participants in terms of age, circumstances, and semester level. Non-parametric statistics were used to assess the significance of the relationship between age, circumstances, and semester variables for dating safety. Some of them have even been prominent in sexual relations. These facts were caused by unregulated environments. In Ruteng, the boarding houses do not have a construction permit because they do not have local regulations from the Manggarai regency government. This confirms the owner's mentality that is oriented to money and ignore the rules, do not limit male and female relations of boarders, and the desire of teenagers to make boarding as a safe dating place. The results of this study are expected to be a reference for local governments to issue local regulations.